Fragments of a History in a Dream - Brant, Clare (Romanticism on the Net, 2023)
This suite of poems, mostly inspired by objects in RÊVE (Romantic Europe: The Virtual Exhibition), engages with Romantic themes, voices, and forms to make playful literary reflections on materiality. They speak about how objects speak to us perfectly and imperfectly, how new and old words translate and transpose, and how poetry can renew lingering romantic echoes.